Effects of Marine Residue-Derived Fertilizers on Strawberry Growth, Nutrient Content, Fruit Yield and Quality - Molosag, Ailin; Parvulescu, Oana Cristina; Ion, Violeta Alexandra; Asanica, Adrian C; Soane, Raluca; Mot, Andrei; Dobrin, Aurora; Frîncu, Mihai; Løes, Anne-Kristin; Cabell, Joshua; Salifoglou, Athanasios; Maroulis, Marios; et al. (Agronomy, 2023)
An outdoor experiment was performed for six months to evaluate the effects of organic fertilizers obtained from marine residual materials on strawberry plants. Three types of organic fertilizers were used, i.e., cod (Gadus morhua) bone powder, common ling (Molva molva) bone powder, and pellets obtained by mixing small cod bone powder and rockweed (Ascophyllum nodosum) residues. A tabletop system for strawberry cultivation was designed, in which two bare-root strawberry plants of cultivar ‘Albion’ were planted in a peat substrate in each pot. Five treatments were applied, i.e., cod bone powder (F1), common ling bone powder (F2), small cod bone powder and rockweed residue pellets (FA), chemical fertilizer (E), and a control (C). The number of leaves and their nutrient content, fruit yield and quality characteristics of the strawberries grown using the organic fertilizers were similar or better than those corresponding to treatments E and C. Organic fertilizers derived from the residues of fish and macroalgae could be a promising alternative to chemical fertilizers in strawberry production.